Effects of Dietary Inclusion of Avocado Seeds on Performance, Nutrient Digestibility, Plasma Biochemical Profile, and Carcass and Meat Traits of Growing Pigs - Consolación García-Contreras; Ana Haro; Manuel Lachica; Isabel Seiquer; Luis Lara; Ignacio Fernández-Fígares; Rosa Nieto (Animals)
Avocado seeds (which are discarded during fruit processing) generate residue that could be utilized in pig feeding. The objective of this study was to test the effects of dietary inclusion of dried-milled avocado seeds (DAS) on pig performance, nutrient and energy digestibility, plasma biochemical parameters, and carcass and meat traits. Twenty-four Landrace × Large White barrows (24 kg body weight, BW) were randomly allocated to three experimental treatments: control diet (CO; 18% CP, 1.12% Lys, and 14 MJ ME/kg), and two diets in which 100 or 200 g DAS/kg partially replaced a CO diet (S10 and S20, respectively). Pigs were individually housed (22 ± 1 °C), and feed and water were provided ad libitum. Animals were weighed weekly and individual intake was monitored daily. The total tract apparent digestibility (TTAD) and nitrogen balance were determined. The experiment ended at 40 kg BW, when the animals were slaughtered for blood and tissue sampling. Voluntary feed intake was not affected by the addition of up to 200 g DAS/kg to the diet. However, growth, nutrient TTAD, and nitrogen retention were depressed at the highest DAS inclusion level. The nutritional characteristics of longissimus lumborum muscle were not affected by DAS ingestion. The inclusion of up to 100 g DAS/kg in the diets of growing pigs could be used to add value to this waste product.